Life style risk factors for femoral neck fracture in Dr. Sardjito Hospital - Helmiza Fahry; Sugeng Yuwana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
As life expentancy improved, the incidence of femoral neck fracture, as one of the mostcommon traumatic injuries in the elderly, has also increased. Risk for fracture is not onlydetermined by age and sex but also by the degree of osteoporosis and certain life-styles.The purpose of this study was to investigate life-style risk factors for femoral neck fracturein Dr. Sardjito General Hospital, Yogyakarta. In this case-control study, all patients withfemoral neck fractures admitted to the Orthopedic Division and Traumatology, Departmentof Surgery in 2013 – 2014 was included as cases. Controls were subjects withoutfracture of similar age and sex. Data of corticosteroid use, habitual coffee consumption,visual acuity disorders, habitual use of slippers and engagement in routine sport activitywere collected with questionnaires. We invited 63 patients (51 females and 12 males)and 63 controls. Corticosteroid use, habitual coffee consumption, visual acuity disorderand habitual use of slippers were risks factors for fractures, OR (95% CI) = 7.5 (2.9-21.6), p < 0.001; 7.5 (2.9-21.6), p < 0.001; 3.2 (1.6-6.8), p < 0.001 and 5.7 (2.7-12.6), p < 0.001, respectively. Engagement in routine sport activity was a protectingfactor, OR (95% CI) = 0.10 (0.02-0.33), p < 0.001. In conclusion, corticosteroid use,habitual coffee consumption, visual acuity disorder and habitual use of slippers are riskfor fractures, while engagement in routine sport is a protecting factor